Digital Libraries The Era of Big Data and Data Science 16th Italian Research Conference on Digital Libraries, IRCDL 2020 - Ceci, Michelangelo; Ferilli, Stefano; Poggi, Antonella (Springer Nature, 2020)
16th Italian Research Conference on Digital Libraries, IRCDL 2020, Bari, Italy, January 30-31, 2020, Proceedings